2013
DOI: 10.1002/ps.3484
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and larval movement of Diatraea saccharalis (Lepidoptera: Crambidae) in seed mixes of non-Bt and Bt pyramid corn

Abstract: The results of this study show that refuge plants in a seed mixture may be able to provide a comparable refuge population of D. saccharalis to a structured refuge planting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 28 publications
3
27
0
14
Order By: Relevance
“…Knowledge of oviposition behavior and larval movement of target pests is also useful for developing effective IRM strategies for Bt crops (Davis and Onstad, 2000;Mallet and Porter, 1992;Goldstein et al, 2010;Burkness et al, 2011;Ives et al, 2011;Onstad et al, 2011;Razze and Mason, 2012;Wangila et al, 2013). For example, if a target species prefers to oviposit more eggs on non-Bt corn than Bt corn plants, and if there is only limited movement of the insect, an RIB planting could be more effective in providing refuge populations compared to structured refuge plantings.…”
Section: Discussionmentioning
confidence: 97%
“…Knowledge of oviposition behavior and larval movement of target pests is also useful for developing effective IRM strategies for Bt crops (Davis and Onstad, 2000;Mallet and Porter, 1992;Goldstein et al, 2010;Burkness et al, 2011;Ives et al, 2011;Onstad et al, 2011;Razze and Mason, 2012;Wangila et al, 2013). For example, if a target species prefers to oviposit more eggs on non-Bt corn than Bt corn plants, and if there is only limited movement of the insect, an RIB planting could be more effective in providing refuge populations compared to structured refuge plantings.…”
Section: Discussionmentioning
confidence: 97%
“…The advantages of RS in sequential feedings on non‐Bt and Bt plant tissue could have important implications for resistance management. In the field, maize borer larvae can feed and move frequently among plants, especially during the early larval stages (Ross & Ostlie, ; Mallet & Porter, ; Davis & Onstad, ; Bell et al., ; Goldstein et al., ; Burkness et al., ; Wangila et al., ; Oyediran et al., ). For example, Ross & Ostlie () reported that more than half of O. nubilalis neonates could abandon the primary host plants and disperse to other plants during the first 2 days after hatching.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, later stages of maize borer larvae (from third instars on) in the field also can move among plants (Mason et al., ). Field observations show that larvae of D. saccharalis and O. nubilalis have the ability to move across several plants within a row of plants as well as to adjacent rows (Mason et al., ; Davis & Onstad, ; Walker et al., ; Wangila et al., ; Oyediran et al., ). In either case, our results suggest that the larval dispersal behavior of maize borers could result in survival and successful reproduction of RS populations in seed mix plantings of non‐Bt and Bt maize plants even with high dose expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations